Coix Seed Oil Exerts an Anti–Triple-Negative Breast Cancer Effect by Disrupting miR-205/S1PR1 Axis - Fang, Ting; Jiang, Yi-Xin; Chen, Long; Huang, Ling; Tian, Xin-Hui; Zhou, Yu-Dong; Nagle, Dale G.; Zhang, Dan-Dan (Frontiers in Pharmacology, 2020)
Coix Seed Oil (CSO) possesses a wide range of pharmacological activities. Kanglaite Injection, a commercial product of CSO, has been used clinically as an anticancer drug in China for decades. However, its molecular mechanisms on triple-negative breast cancer(TNBC) remains to be elucidated. In this study, the effect of CSO was evaluated on murine TNBC 4T1 cells and the orthotopic tumor-bearing mouse model and underlying mechanisms were explored. CSO suppressed cell proliferation, colony formation in vitro, and tumor growth in vivo. miR-205-5p was substantially altered in CSO treated tumor tissues compared to the control group by miRNA-sequencing analysis. Sphingomyelin metabolism (SM) decreased in serum in model group compared to the control group, while it increased by CSO administration by lipid metabolomics analysis. The expression of sphingosine 1 phosphate receptor 1 (S1PR1), the critical effector of SM, was downregulated upon CSO treatment. Mechanically, miRNA-205 directly targeted S1PR1 to regulate SM and cell proliferation. CSO reduced the expression of S1PR1, cyclinD1, and phosphorylation levels of STAT3, MAPK, and AKT while upregulated p27. These results revealed that CSO exerted an anti-TNBC effect via the miR-205/S1PR1 axis to regulate sphingomyelin metabolism, and the downstream STAT3/MAPK/AKT signal pathways were partly involved.